Do sentences affect public disapproval? - Walker, Nigel (The British journal of criminology, 1984)
The belief of some judges that in sentencing “the main duty of the courts is to lead public opinion” (R. v. Sargeant) implies that the choice of sentence influences public approval or disapproval of law-breaking. To test this, 1,055 parents in three English towns were interviewed. Since it is only through the news media that the public can be influenced by sentence, their recollections of reports of criminal trials were tested. Only 39 per cent. could recall a single sentence, and only 13 per cent. could recall two sentences. In the experimental part of the interview respondents were shown five specially designed newspaper cuttings describing criminal incidents, but not mentioning the courts' sentences. Respondents were randomly assigned to one of four sub-samples, so that after studying each cutting they were given different information about the type of sentence (prison or probation), the judge's view (severe or lenient) or the degree of disapproval of “people like yourself” (“strongly” or “a little”). They were then asked to indicate, on a seven-point verbal scale, how much they themselves disapproved of what the offender did. Thus even respondents on whom newpaper reports of sentences made little or no impression were obliged to take note of the sentence. The main findings were that information about the type of sentence or the judge's view of the offence did not influence enough respondents to produce a significant difference in mean disapproval scores; and that telling respondents about the disapproval level of “people like yourself” influences them only when the newspaper cutting involved a morally ambiguous incident. By contrast, when asked how much they disapproved of “deciding not to wear a seat-belt” “at the moment” and “when it becomes an offence”, respondents' mean disapproval levels were significantly higher for “when it becomes an offence”: a finding which is consistent with earlier research.